KUALITAS PERKAWINAN DAN LINGKUNGAN PENGASUHAN PADA KELUARGA DENGAN SUAMI ISTRI BEKERJA - Rizkillah, Risda; Sunarti, Euis; Herawati, Tin (Jurnal Ilmu Keluarga dan Konsumen, 2015)
Increase of women’s labor force participation in public sector causes double burden for women to divide their time between work and family. Imbalance between work and family potentially reduce marital quality and parenting environment quality. This study aimed to analyze the influence of family and wife’s job characteristic and marital quality on parenting environment quality in dual earner families. The sample in this study were working wive that had children aged 0-6 years old and taken by stratified nonproportional random sampling; involved 120 wive of dual earner families. The data was collected by interviewing the wife using a questionnaire. The results showed that the attainment of marital quality reached 75,7; it’s mean that marital quality of the family was in good enough category. Organizing the environment (83,9) and academic stimulation (86,6) were the components with the highest attainment in parenting environment quality. Parenting environment quality had positive correlation with marital quality, wife’s education, family income per capita; but had negative correlation with family size. Regression analysis showed that parenting environment quality influenced by family and wife’s job characteristic and marital quality (R2=0,425).